2005
DOI: 10.1373/clinchem.2004.046565
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Specific IgE Measured by a Continuous Random-Access Immunoanalyzer: Interassay Comparison and Agreement with Skin Testing

Abstract: Background: Our aims were to evaluate the performance of a fully automated system for measuring circulating allergen-specific IgE (sIgE) against an established in vitro assay and to assess the system's diagnostic accuracy against objective clinical criteria for identifying sensitization to specific allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…This is consistent with several studies which found a good agreement between SPT and sIgE in developed [42][43][44] and in an urban area of developing country [45]. However, no significant association was observed in the low-SES which is in line with our previous study conducted in a rural area of Indonesia where a dissociation between sIgE levels to aeroallergens and skin prick test to the same allergens was found [2].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with several studies which found a good agreement between SPT and sIgE in developed [42][43][44] and in an urban area of developing country [45]. However, no significant association was observed in the low-SES which is in line with our previous study conducted in a rural area of Indonesia where a dissociation between sIgE levels to aeroallergens and skin prick test to the same allergens was found [2].…”
Section: Discussionsupporting
confidence: 92%
“…All of the sera of the first two groups were derived from patients with a history of a systemic allergic reaction after a stinging event. sIgE tests for HBV or YJV were performed in all of the patients on the automated immunoassay systems UniCAP250 (Phadia, Uppsala, Sweden) or Immulite2000 (Siemens Healthcare Diagnostics) as described in detail elsewhere (21). For further investigation of Api m 5/Ves v 3 serologic IgE reactivity and for basophil activation tests with recombinant venom allergens, patients with a suspected history of an allergic reaction to Hymenoptera stings were consecutively recruited during routine allergy diagnostic workup (n = 25).…”
Section: Characterization Of Venom-allergic Patientsmentioning
confidence: 99%
“…A person who has an allergy usually has an elevated level of IgE in blood, therefore the quantification of IgE can considerably ease the clinical diagnosis of allergymediated disorders (Gokulrangan et al 2005). Although the detection of IgE was already possible thanks to methods such as radioimmunoassay (RIA) or enzyme-linked immunosorbent assay (ELISA) (Peuravuori & Korpela 1993;Ollert et al 2005), this aptasensor offers a fast and cheap detection method requiring less serum sample and reagents. The use of this aptamer as a recognition element of the sensor enables detection of concentrations as low as 2.5 µg/L of IgE in buffer and serum In this sensor, a 5'-biotin modified nucleic acid aptamer has been fixed to an avidin modified gold layer of a quartz crystal microbalance device (QCM), providing a strong immobilisation of the recognition element.…”
Section: Mass Based Detection Of Human Igementioning
confidence: 99%